POTENSI DAN MASALAH WISATA PAHLAWAN KOTA SURABAYA - Rojil Nugroho Bayu Aji (Program Studi Pendidikan Sejarah - Universitas Samudra, 2014)
Surabaya is the second biggest city in Indonesia and known as the city of hero. That titleacquired for long history in Surabaya, during struggle of Indonesia independence from colonialism,especially in the battle of 10th November 1945. This history must be kept, so that next generation caninherit it as important historical insight.Surabaya is rich of historical sites that can be used for learning. By historical approach, it isalso possible to take wisdom of inherent values in those sites. This learning can be done by herotourism. Through this tourism, important historical values are possible to transform to public society,directly or indirectly.For example, Surabaya has HOS Cokroaminoto’s residence and boarding house. Soekarnoand Sema’oen used to stay in that boarding house. Both places are cultural conservation, but not usedoptimally yet as historical tourism object. Surabaya also has hero cemetery, such as cemetery of Dr.Sutomo, the founder of Budi Utomo, cemetery of Bung Tomo, the great orator in the battle of 10thNovember 1945, and cemetery of W.R. Supratman, the composer of national anthem, Indonesia Raya.All those names are Indonesian national heroes, and those historical buildings protected underSurabaya city government, as cited in The Decree of Surabaya Mayor in 1966 and 1998. That decreeconsists of 163 buildings and sites that must be protected. Moreover, Surabaya also has Museum ofHero Monument, a high value historical site. This museum is used frequently for historical visit inSurabaya, related its title as the city of hero.It is not impossible, Surabaya will have complete feature as the city of hero, and also as a citythat appreciate heroes’ sacrifices, as long as its potential has been used optimally and its problems hasbeen solved.